Inovasi Kurikulum Berbasis Alam Pada Masa Pandemi Covid-19 - Nur Hakim, Muhammad; Sari, Nehlia (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2023)
MI Alam Luqman Al Hakim Hidayatullah Batu is one of the Natural schools in Indonesia. With that curriculum, innovation is something that cannot be avoided in interacting with the educational environment as an improvement in the learning process in schools, especially during a pandemic. Researchers used descriptive qualitative research, data collected through interviews, observation, and documentation methods to test the validity of the data by data triangulation. And data analysis techniques a) data reduction b) data presentation c) drawing conclusions. The research subjects were madrasah, waka curriculum, MI Alam teacher Luqman Al-Hakim Hidayatullah Bata. The results of this study indicate that the educational curriculum innovation at MI Alam Luqman Al-Hakim Hidayatullah Batu shows that (1) providing programs or activities in the learning process (2) obstacles that occur due to changes in the learning process due to the covid-19 pandemic (3) Solutions provided by schools namely providing a program of activities in the learning process that is creative and innovative so that children remain fun even though the learning process is at home and also provides motivation to children. His suggestion is MI Alam Luqman Al-Hakim Hidayatullah to be more creative and innovative in guiding children and in carrying out the learning process.